Memoirs of My Life and Writings - Gibbon, Edward, 1737-1794 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of My Life and Writings" by Edward Gibbon is an autobiography compiled in 1796 from six fragmentary works written during his final years. This pioneering memoir traces Gibbon's journey from his disappointing Oxford education through his conversion to Catholicism, his time in Switzerland, and his service in the Hampshire militia. The narrative culminates in his famous moment of inspiration amid Rome's ancient ruins, where he conceived his monumental history of the Roman Empire's decline and fall, offering intimate glimpses into the making of a great historian. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Memoirs_of_My_Life_and_Writings
Release date is 2004-07-01
Produced by P. J. Riddick and David Widger
Keywords: Historians -- Great Britain -- Biography; Gibbon, Edward, 1737-1794